The Reduced Expression of EOLA1 May Be Related to Refractory Diabetic Foot Ulcer - Mingxia Wu; Weiling Leng; Hang Pan; Xiaotian Lei; Liu Chen; Xinshou Ouyang; Ziwen Liang (Mediators of Inflammation)
Background. Chronic diabetic foot ulcer (DFU) is one of the most intractable complications of diabetes mellitus (DM). Its pathogenesis is complex, and uncontrolled chronic inflammation is an important factor. Endothelial overexpressed lipopolysaccharide-associated factor 1 (EOLA1) discovered in our laboratory is an intracellular protein with the function of inflammatory regulation. This study was aimed at observing the expression of EOLA1 in DFU skin tissues and its relationship with inflammation and at exploring the possible role of EOLA1 in DFU and its mechanism. Methods. The patients with DFU were divided into 2 groups based on the formation time of ulcer: the acute wound (AW) group with the course of disease≤4 weeks and the chronic wound (CW) group with the course of disease>4 weeks. The relevant clinical data of patients were collected, and the skin tissues around the ulcer were used for immunofluorescence detection and immunohistochemical staining to observe inflammation. The expression levels of EOLA1, metallothionein 2A (MT2A), nuclear factor-κB (NF-κB), and interleukin-6 (IL-6) were detected by western blot. Results. A total of 79 patients were enrolled in the study. The results of immunofluorescence and immunohistochemistry showed that EOLA1 was expressed in the epithelial tissues of DFU. However, the expression of EOLA1 in the CW group was significantly lower than that in the AW group (P<0.05), and the expression of NF-κB and IL-6 was obviously increased (P<0.05). Conclusion. The refractory wounds in patients with DFU may be closely related to the uncontrolled activation of inflammatory pathways in cells caused by the reduced expression of negative regulators of inflammation (e.g., EOLA1), and such decreased expression may be also strongly linked to the persistent state of inflammation.